2015
DOI: 10.1016/j.ajpath.2014.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Activation of Atypical Protein Kinase C in Carbon Tetrachloride–Induced Oxidative Stress Provokes a Disturbance of Cell Polarity and Sealing of Bile Canalicular Lumen

Abstract: Polarized hepatocytes contain tight junctions (TJs), which are among the most important junctions for sealing the bile canalicular lumen from the sinusoidal space. Alterations in TJs are implicated in chronic cholestatic liver diseases, such as primary biliary cirrhosis and primary sclerosing cholangitis, which have lipid peroxidation marker elevations or antioxidant vitamin decreases. However, the effect of oxidative stress on hepatocyte polarity or liver morphology is unknown. We found that carbon tetrachlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…This suggests that APAP toxicity, via oxidative stress, may involve a PKC-dependent signalling pathway 62 . PKC involvement is also observed in other cell types, including bronchial epithelial cells 63 , and in vivo following carbon tetrachloride (CCl 4 )-induced oxidative stress in rat liver 50 . PKC signaling is also shown to play an important role in Clostridium difficile toxin A-mediated damage on TJ structure and functions in human colonic cells 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that APAP toxicity, via oxidative stress, may involve a PKC-dependent signalling pathway 62 . PKC involvement is also observed in other cell types, including bronchial epithelial cells 63 , and in vivo following carbon tetrachloride (CCl 4 )-induced oxidative stress in rat liver 50 . PKC signaling is also shown to play an important role in Clostridium difficile toxin A-mediated damage on TJ structure and functions in human colonic cells 53 .…”
Section: Discussionmentioning
confidence: 99%
“…1e ). Interestingly, recent work shows that CCl 4 -induced oxidative stress in rats, resulted in disassembly of TJ and depolarization of hepatocytes, through disruption of atypical-PKC complex formation, evident after only 2 hours of CCl 4 -leading to liver cholestasis and cirrhosis 50 . Indeed, given atypical-PKC regulates TJ assembly and epithelial cell polarity, it is feasible that APAP-induced oxidative stress may also lead to dysregulation of TJ-mediated cell-signaling and membrane trafficking 51 , particularly at a high-dose of APAP, resulting in cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The commercially available antibodies were as follows: anti‐annexin II (Clone 5) mouse monoclonal antibodies (mAbs) (BD Biosciences, San Jose, CA); anti‐aPKCζ (C20) rabbit polyclonal antibody (pAb), anti‐glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH; 6C5) mouse mAb, and mouse–rabbit–rat control IgG (Santa Cruz Biotechnology, Santa Cruz, CA); anti‐Par‐3 rabbit pAb (Merck Millipore, Darmstadt, Germany); anti‐BrdU mouse mAb (Medical & Biological Laboratories Co., Ltd., Nagoya, Japan); anti‐phospho‐aPKCζ T560 rabbit mAb (Abcam Ltd., Cambridge, UK); anti‐phospho‐Akt S473 (#4060S); and anti‐Akt (#9272) rabbit mAbs, and anti‐β‐actin rabbit pAb (#4967) (Cell Signaling Technology, Beverly, MA); horseradish peroxidase‐conjugated secondary Ab (GE Healthcare Bio‐Sciences, Piscataway, NJ). The phospho‐specific mouse mAb against S653 of human lethal (2) giant larvae (Llgl2) was produced against a phospho‐peptide [KSLRES(P)FRKLR] as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…IP‐kinase assay was performed as described previously . The cells were harvested and lysed in IP lysis buffer (20 mM Tris–HCl, pH 7.4, 0.25 M sucrose, 1.2 mM EDTA, 20 mM β‐mercaptoethanol, 150 mM NaCl, 1 mM NaF, 1 mM Na 4 P 2 O 7 , 0.5% Triton X‐100, 0.5% Nonidet P‐40, 0.001% aprotinin, and 1 mM PMSF).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study has shown that induction in oxidative stress by administration of carbon tetrachloride disrupted Par-3 – alpha-PKC complex formation resulting in disassembly of TJ and depolarization of hepatocytes. These changes led to cholestasis and cirrhosis [147] . The mobilization of fibrogenic cells has been proposed to involve conversion of polarized hepatocytes and biliary epithelial cells into mesenchymal cells with concomitant loss of epithelial polarization and acquisition of a mobile phenotype, but this is controversial [148,149] .…”
Section: Hepatocyte Polarity Determinants and Acquired Liver Diseasesmentioning
confidence: 99%